Factors Associated with Nutrition of 12-59 Months Toddlers - Tunik Mindarwati Ningsih; Koekoeh Hardjito; Triatmi Andri Yanuarini (STIKes Patria Husada Blitar, 2022)
Malnutrition is still a problem in developing countries, including Indonesia, which ranks 4th with the incidence of malnutrition is still high. Toddlers with malnutrition can continue to be malnourished, impaired physical and mental growth and even increase the risk of illness and death. The purpose of this study was to review journals related to factors of malnutrition of children aged 12-59 months in developing countries. The research design was a literature review using a systematic mapping study method. There were 602 articles obtained and the number of articles selected based on inclusion and exclusion criteria was 13 articles. Accredited and reputable article database from PubMed, DOAJ, Research Gate 1, and SINTA were then analyzed using the compare method. There were 16 factors related to undernutrition status in developing countries including the age of children more than 2 years, sex of male toddlers, low birth weight of children, not being given exclusive breastfeeding, inadequate nutritional intake, disease or infection, low maternal education, low fathers education, lack of knowledge of maternal nutrition, inappropriate eating parenting patterns, low family income or wealth index, rural areas, low maternal BMI, maternal age less than 20 years, non-routine ANC visits, access to drinking/clean water and poor sanitation. It was found that the dominant factor appeared and had a significant correlation, namely the age of toddlers over 2 years was more at risk of experiencing malnutrition and the factor of low maternal education would further increase the possibility of malnutrition in toddlers. The causes of undernutrition in children under five are very complex where there are many related factors, there are also dominant factors that can also be paid more attention to in order to prevent and minimize the incidence of malnutrition